(untitled) - Bucholtz, Rikke Hagstrom (Denmark, 2005)
The thesis consists of a general introduction, four separate papers concerning biology and utilization of the mudskipper pseudapocryptes elongatus and finally conclusions and recommendations for future management and research.
Keywords: Mudskippers,Cá kèo; Research,Nghiên cứu; Mekong River Delta,Đồng bằng Sông Cửu Long